Pride, prejudice, and peril - Oliver, Katie (A Jane Austen Tea Society mystery., 2021)
Phaedra Brighton is perfectly content with her life of lecturing college students, gossiping with her best friends, and dreaming of Mr. Darcy. As a young, respected (if somewhat peculiar) English professor, her expertise lies in all things Jane Austen but she knows that the closest she'll ever get to being a real-life Elizabeth Bennet is in her dreams. With murder on the syllabus and her best friend in dire straits, there's no Mr. Darcy around to help Phaedra-- she'll have to get to the bottom of this mystery herself."